Archetypal Representation of “Draupadi” in The Mahabharat: A Feminist Inquiry into the Hindu Myth: Representação arquetípica de “Draupadi” no Mahabharat: uma investigação feminista sobre o mito hindu - Adhikary, Ramesh Prasad (NJINGA e SEPÉ: Revista Internacional de Culturas, Línguas Africanas e Brasileiras (ISSN: 2764-1244), 2024)
The prevalence of "feminism" across literary, digital, and academic platforms underscores its importance in contemporary discourse. This era is characterized by an increased focus on feminist principles and their societal applications. The Mahabharat, a popular Hindu epic of Indian Sub-continent; with its intricate characters and plotlines, has inspired extensive interpretations from various perspectives. Among its characters, Draupadi stands out as a significant symbol of female empowerment and resilience against adversity. This study aims to analyze Draupadi's character, emphasizing her role as a symbol of feminist strength within The Mahabharat. Employing subversion theory, the research explores how Draupadi challenges traditional gender roles and societal expectations. Methodologically, this study conducts a textual analysis of Draupadi's portrayal, examining instances of her assertiveness, compassion, and unwavering commitment to justice. The analysis focuses on her resistance to injustice, particularly regarding her rights as a daughter-in-law and the Pandavas' entitlements. Findings reveal that Draupadi embodies a complex and multifaceted character, challenging conventional gender norms and providing a nuanced perspective on female agency. Her actions and resilience highlight her as a figure of immense significance in Hindu literature. In conclusion, Draupadi's portrayal transcends traditional gender roles, offering a compelling narrative of empowerment and resistance. This study elucidates her enduring legacy and relevance as a feminist icon, reaffirming the significance of feminist ideals in contemporary society. *** A prevalência do "feminismo" em plataformas literárias, digitais e acadêmicas ressalta sua importância no discurso contemporâneo. Esta era é caracterizada por um foco maior nos princípios feministas e suas aplicações sociais. O Mahabharat, um épico hindu popular do subcontinente indiano; com seus personagens e enredos intrincados, inspirou interpretações extensas de várias perspectivas. Entre seus personagens, Draupadi se destaca como um símbolo significativo do empoderamento feminino e da resiliência contra a adversidade. Este estudo visa analisar a personagem de Draupadi, enfatizando seu papel como um símbolo da força feminista dentro do Mahabharat. Empregando a teoria da subversão, a pesquisa explora como Draupadi desafia os papéis tradicionais de gênero e as expectativas sociais. Metodologicamente, este estudo conduz uma análise textual do retrato de Draupadi, examinando instâncias de sua assertividade, compaixão e compromisso inabalável com a justiça. A análise se concentra em sua resistência à injustiça, particularmente em relação a seus direitos como nora e aos direitos dos Pandavas. As descobertas revelam que Draupadi incorpora uma personagem complexa e multifacetada, desafiando normas de gênero convencionais e fornecendo uma perspectiva diferenciada sobre a agência feminina. Suas ações e resiliência a destacam como uma figura de imensa importância na literatura hindu. Concluindo, o retrato de Draupadi transcende os papéis tradicionais de gênero, oferecendo uma narrativa convincente de empoderamento e resistência. Este estudo elucida seu legado duradouro e relevância como um ícone feminista, reafirmando a importância dos ideais feministas na sociedade contemporânea.